Investigating the mechanisms of Sini San in alleviating inflammatory responses via multi-omics and the BDNF/TrkB/PI3K/AKT signaling pathway in depressive model rats - Zeng, Jia-Wei; Han, Zhen-Jie; He, Xiu-Tang; Liu, Xue-Jiao; Wang, Hui-Yue; Yang, Shu-Sheng; Bai, Jing; Duan, Yan-Jun; Lin, Li (Frontiers in Psychiatry, 2025)
BackgroundSini San, from the traditional Chinese medicine classic Treatise on Exogenous Febrile Disease, has been reported to improve anxiety and depressive symptoms in clinical practice and exhibits certain anti-inflammatory effects. Studies have shown that the inflammatory response is not merely a concomitant feature of depression but actively contributes to its pathogenesis via neuroimmune mechanisms. However, the underlying mechanism remains unclear.AimThis study aimed to evaluate the antidepressant effect and inflammatory profile of Sini San in chronic unpredictable mild stress (CUMS)-induced rats and to explore its potential mechanism.MethodsThe primary active ingredients, targets, and pathways of Sini San in treating depression were determined through network pharmacology. The improvement of depression-like behaviors was assessed using behavioral experiments. Tissue inflammatory responses were evaluated through histopathological analysis (HE staining and Nissl staining) and quantitative measurement of inflammatory cytokines by ELISA. Western blotting (WB) was employed to quantify protein expression levels, while RT-qPCR was used to assess mRNA transcription levels. Gut microbial composition was analyzed by 16S rRNA gene amplicon sequencing, with taxonomic classification performed using the Greengenes database.ResultsThe data indicated that Sini San reduced inflammation related to the NLRP3 inflammasome pathway by inhibiting the expression of NLRP3, ASC, caspase-1, and downstream pro-inflammatory cytokines IL-18, IL-1β, and TNF-α. According to network pharmacology analysis, Sini San mitigated depression via modulation of the PI3K/AKT signaling pathway. Upstream and downstream proteins, including BDNF (brain-derived neurotrophic factor), TrkB (tropomyosin receptor kinase B), and p-CREB (phosphorylated cAMP response element-binding protein), which were decreased after CUMS induction, were regulated by Sini San. Furthermore, Sini San enhanced the expression of colonic tight junction and adhesion junction proteins ZO-1, claudin-1, and occludin-1 mRNA, while simultaneously restoring intestinal microbiota balance—indicating amelioration of CUMS-induced disruptions in intestinal barrier function and microbial composition.ConclusionSini San modulates the gut–brain axis by inhibiting the NLRP3 inflammasome, thereby alleviating CUMS-induced inflammation and gut microbiota dysbiosis in rats. This effect may further contribute to the improvement of depressive symptoms via regulation of the BDNF/TrkB/PI3K/AKT signaling pathway.